Analisis Pasar dalam Perencanaan Pembangunan Sentra Wisata di Desa Mlokorejo - Rofiud Darajah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyse the market for planning the development of a tourism center in Mlokorejo Village, which is renowned for its appealing natural and cultural assets. Employing a mixed-methods approach, the research combines qualitative and quantitative methods through surveys, in-depth interviews, and literature reviews. The primary findings reveal that Mlokorejo Village possesses significant natural attractions, including hills, terraced rice fields, and clear rivers, as well as rich cultural elements such as local traditions, traditional arts, and unique cuisine. Market segmentation identifies local, domestic, and international tourists as potential targets, each with different preferences ranging from nearby recreational activities to authentic cultural experiences. Current tourism trends indicate a growing interest in ecotourism and community-based tourism, which should be integrated into product development. The study also highlights that the existing infrastructure and facilities are insufficient, with improvements needed in accommodation, transportation, and public amenities. Furthermore, local community support and empowerment are crucial for the project's success, with training and active involvement being key components of the development strategy. In conclusion, with an integrated and data-driven approach, Mlokorejo Village has significant potential to become a successful tourist destination, offering substantial economic and social benefits to the local community while supporting cultural and environmental sustainability.